KEDUDUKAN HUKUM PEMEGANG HAK TANGGUNGAN ATAS TANAH HAK GUNA BANGUNAN DI ATAS TANAH NEGARA YANG JANGKA WAKTUNYA TELAH BERAKHIR - Ardiyanto Ardiyanto (Trunojoyo Madura University, 2022)
The current positive law no longer allows HGB to be extended continuously, and must return to state land. One of the reasons for the loss of mortgage rights is related to the expiration of the HGB. The purpose of this study is to analyze the legal consequences and legal protection for creditors holding mortgage rights after the HGB expires. The results of the research are that the lex posteriori derogat lex priori principle results in PP 18/2021 which is in the hierarchy of the Job Creation Law to override old regulations that are at the same level as government regulations. With the implementation of Article 37 PP 18/2021 there is a gap in the position of banks as preferred creditors to become concurrent creditors because the HGB has returned to become state land. In non-litigation efforts by regulating clauses related to extension, renewal and re-application of HGB in credit agreements that are preventive in nature against Article 37 PP 18/2021. Litigation efforts against the abolition of mortgage rights must be carried out in a default suit or unlawful act.